2017
DOI: 10.1002/cb.1698
|View full text |Cite
|
Sign up to set email alerts
|

How consumers “see” a visually warm store: Differences between affective and cognitive processors

Abstract: Store atmosphere can influence shoppers' perceptions and behaviors. This research contributes to the literature by showing that a visually warm store atmosphere can induce psychological warmth perception among in‐store consumers. An empirical study was conducted to investigate the effect of warmth through a visually warm or cold store atmosphere on consumers' perceptions/behaviors and the moderating role of consumers' processing styles. Results (N = 181) showed that a visually warm (vs. cold) atmosphere induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…Yoo, Park and Macinnis (1998) revealed that environmental factors, such as temperature, lighting, interior decoration, design and facility layout, could directly affect the revisiting of customers in the service space [20]. In addition, Baek et al (2018) found that a shop's atmosphere influences shoppers' perceptions and behaviors [21]. That is, a warm visual atmosphere can induce psychological warmth between the store and the customer.…”
Section: Physical Environment and Customer Satisfactionmentioning
confidence: 99%
“…Yoo, Park and Macinnis (1998) revealed that environmental factors, such as temperature, lighting, interior decoration, design and facility layout, could directly affect the revisiting of customers in the service space [20]. In addition, Baek et al (2018) found that a shop's atmosphere influences shoppers' perceptions and behaviors [21]. That is, a warm visual atmosphere can induce psychological warmth between the store and the customer.…”
Section: Physical Environment and Customer Satisfactionmentioning
confidence: 99%
“…The warm colors in the environment can also prompt people to have trust, positive attitudes, and behavioral intentions in the target objects (Choi et al, 2016). The research of Baek et al (2018) also supported that store atmosphere and visual warmth can induce consumers' psychological warmth and have a positive incentive effect on consumers' purchasing decisions. This kind of visual warmth brought by warm colors is produced without physical warmth (Macrae et al, 2013), so it is also applicable to pictures (Rai et al, 2017).…”
Section: Analysis and Discussion Of Warm And Cold Colors And Model Ba...mentioning
confidence: 67%
“…As in general color psychology, if applied to context management, depending on where the color is applied, it is important to consider whether it is applied to: (a) structural or architectural components or (b) other physical components, such as furniture (Baek et al, 2018). Structural or architectural components.The architectural components that can define the interior of a space and, therefore, can provide its own characteristics are the walls, ceilings and floors. The wall is a structural component of the space that makes it possible to delimit spaces, but this component, not only has a functional nature within the space, but it also possesses an esthetic function (Ching & Binggeli, 2011; Mesher, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As in general color psychology, if applied to context management, depending on where the color is applied, it is important to consider whether it is applied to: (a) structural or architectural components or (b) other physical components, such as furniture (Baek et al, 2018). a.…”
Section: The Components Of the Commercial Environment: Definition And...mentioning
confidence: 99%